ARTIFICIAL INTELLIGENCE-BASED GOVERNMENT MANAGEMENT TRANSFORMATION IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN THE ERA OF DIGITAL GOVERNANCE - Lalu Ahmad Murdhani (Ninety Media Publisher, 2025)
This study aims to analyze the transformation of government management based on artificial intelligence in improving the quality of public services in the era of digital governance. The study focuses on the use of AI in public-service delivery, administrative decision-making, and bureaucratic efficiency, while also examining the need for accountability and public ethics in its implementation. This research uses a qualitative method with an exploratory-descriptive and conceptual model-building approach. Data were collected through secondary and documentary sources, including recent peer-reviewed journal articles, policy documents, institutional reports, and regulatory materials related to AI governance, digital government, public administration, and public-service innovation. The data were analyzed using thematic analysis to identify key patterns related to AI utilization, organizational readiness, decision-support systems, ethical risks, and accountability mechanisms. The findings show that AI can improve public services through automation, intelligent citizen interaction, complaint classification, document verification, and predictive service delivery. AI also supports bureaucratic efficiency by reducing repetitive administrative tasks, improving data-based decision-making, and strengthening service monitoring. The main contribution of this study is the formulation of an adaptive AI-based government management model consisting of five dimensions: AI-enabled service innovation, data-driven decision support, bureaucratic workflow redesign, human oversight, and ethical-accountable governance. This model emphasizes that AI transformation in government must be supported by institutional capacity, transparent procedures, human supervision, and public-value orientation.